2017
DOI: 10.1007/s15010-017-1002-7
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous detection and identification of STI pathogens by multiplex Real-Time PCR in genital tract specimens in a selected area of Apulia, a region of Southern Italy

Abstract: Our data suggest different patterns of infections between females and male and the importance of an increased vigilance of sexually transmitted pathogens to reduce the burden on general population and the sequelae or the complications on reproductive organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 32 publications
1
17
3
1
Order By: Relevance
“…Lee et al (4) screened 304 women and detected bacteria in 36.5%, most frequently U. urealyticum (14.5%), followed by M. hominis (13.8%). In south Italy, Del Prete et al (9) screened 1272 women and detected at least one bacterium in 30.7% of women. The most commonly detected bacterium was by far U. parvum (25.9%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al (4) screened 304 women and detected bacteria in 36.5%, most frequently U. urealyticum (14.5%), followed by M. hominis (13.8%). In south Italy, Del Prete et al (9) screened 1272 women and detected at least one bacterium in 30.7% of women. The most commonly detected bacterium was by far U. parvum (25.9%).…”
Section: Discussionmentioning
confidence: 99%
“…The coinfection rates in women with and without cervicitis were comparable in our study, concordant with the findings of Gaydos et al (32) . Studies about the detection rates of infectious agents causing vaginitis and cervicitis are summarized in Table 3 (4)(5)(6)9,11,32,39) . In our study, it has been shown that multiplex realtime PCR-NAAT is beneficial for the demonstration of cervical bacterial colonization with commensal pathogens including U. urealyticum, M. hominis, and U. parvum or with pathogens that can cause cervicitis such as C. trachomatis, N. gonorrhea, and M. genitalium.…”
Section: Cervicitismentioning
confidence: 99%
“…Comprehensive testing and subsequent antimicrobial treatment of these three urogenital mycoplasma species in adults are performed in several settings in, e.g., Eastern Europe, Southern Europe, South America and Asia. In many countries, this testing has also increased due to the introduction of multiplex PCR assays detecting traditional non‐viral ‘true’ STI agents together with M. hominis , U. parvum and/or U. urealyticum . These multiplex PCR assays can additionally have suboptimal specificity and/or sensitivity, particularly when home‐sampled and self‐sampled specimens, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In many countries, this testing has also increased due to the introduction of multiplex PCR assays detecting traditional non-viral 'true' STI agents together with M. hominis, U. parvum and/or U. urealyticum. [5][6][7] These multiplex PCR assays can additionally have suboptimal specificity and/or sensitivity, particularly when home-sampled and self-sampled specimens, e.g. using sampling kit purchased on Internet, are analysed.…”
Section: Introductionmentioning
confidence: 99%
“…7 PCR-based approaches have been shown to be more sensitive at detecting pathogens in clinical samples than traditional diagnostic tests (ie, culture, microscopy and antigen detection) if samples are collected at the appropriate time during infection. 3,29 Considering the wide range of etiological agents that can cause STIs and the similarity of the clinical presentations of infection produced by different pathogens, the multiplex molecular diagnostic tools seem to be an optimal method for rapid diagnosis. 2,12,30 Therefore, we utilized multiplex PCR and MALDI-TOF MS incorporated into an STI-MS assay, which might be helpful for better understanding the phenomenon of mixed infections in clinical specimens.…”
Section: Discussionmentioning
confidence: 99%